Age‐related change in renal corticomedullary differentiation: Evaluation with noncontrast‐enhanced steady‐state free precession (SSFP) MRI with spatially selective inversion pulse using variable inversion time. Issue 1 (5th August 2013) - Noda, Yasufumi; Kanki, Akihiko; Yamamoto, Akira; Higashi, Hiroki; Tanimoto, Daigo; Sato, Tomohiro; Higaki, Atsushi; Tamada, Tsutomu; Ito, Katsuyoshi
<x xml:space="preserve">Abstract</x> Purpose To evaluate age‐related change in renal corticomedullary differentiation and renal cortical thickness by means of noncontrast‐enhanced steady‐state free precession (SSFP) magnetic resonance imaging (MRI) with spatially selective inversion recovery (IR) pulse. Materials and Methods The Institutional Review Board of our hospital approved this retrospective study and patient informed consent was waived. This study included 48 patients without renal diseases who underwent noncontrast‐enhanced SSFP MRI with spatially selective IR pulse using variable inversion times (TIs) (700–1500 msec). The signal intensity of renal cortex and medulla were measured to calculate renal corticomedullary contrast ratio. Additionally, renal cortical thickness was measured. Results The renal corticomedullary junction was clearly depicted in all patients. The mean cortical thickness was 3.9 ± 0.83 mm. The mean corticomedullary contrast ratio was 4.7 ± 1.4. There was a negative correlation between optimal TI for the best visualization of renal corticomedullary differentiation and age (r = −0.378; P = 0.001). However, there was no significant correlation between renal corticomedullary contrast ratio and age (r = 0.187; P = 0.20). Similarly, no significant correlation was observed between renal cortical thickness and age (r = 0.054; P = 0.712). Conclusion In the normal kidney, noncontrast‐enhanced SSFP MRI with spatially selective IR pulse can be used to assess renal corticomedullary differentiation and cortical thickness without the influence of aging, although optimal TI values for the best visualization of renal corticomedullary junction were shortened with aging. J. Magn. Reson. Imaging 2014;40:79–83. © 2013 Wiley Periodicals, Inc.